La frange nord-est de Rodumna/Roanne (Loire) : la fouille des 81-83 rue de Charlieu (ier s. av. J.-C.-ive s. ap. J.-C.) - Sylvie Bocquet; Karine Giry (Revue Archéologique du Centre de la France)
The preventive excavation carried out in 2010 by a team of INRAP at 81-83 rue de Charlieu covers 8 163 m² and concerns the genesis and the evolution of the northeastern margin of Rodumna/Roanne (Loire). The first traces of a frequentation of the sector date from the Latenian period and are characterized by a long ditch whose axis is taken again at the beginning of the 1st century AD, during the implantation of a road. The development of this peripheral area operates according to a structured network of various facilities (palisades, ditches, pits) and buildings. A masonry cellar has delivered a reused lapidary inscription mentioning the Emperor Claude and the first painted decor in the “style à candélabre” restituable on Roanne. The general context is essentially domestic but various indications attest the possibility or the proximity of artisanal activities (drying/smoking, in connection with the textile or using alum). After the middle of the 3rd century-4th century, the sector becomes agricultural, until the foundation of the “Carmel de la Republique” (1897). These results, around the morphogenesis of a periurban zone, complete the knowledge of the ancient urban space and give rise to new reflections on the Roanne ceramic.